Facultad de Ciencias Administrativas de la UEB entregó profesionales a la sociedad ecuatoriana - García García, Mariana (2023)
The Faculty of Administrative Sciences, Business Management and Informatics, pleased once again by incorporating 61 professionals from the Communication and Tourism careers and Hospitality, Commercial Engineering and Systems. The academic event was attended by the main authorities of the Faculty Dr. Henry Vallejo, dean, Career Coordinators, members of the Board of Directors; he Mr. Rector Dr. Arturo Rojas, accompanied the solemn graduation ceremony, an event of significance for the State University of Bolívar.